2011
DOI: 10.1200/jco.2011.35.0371
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Minimal Residual Disease in NPM1-Mutated Acute Myeloid Leukemia: A Study From the German-Austrian Acute Myeloid Leukemia Study Group

Abstract: We defined clinically relevant time points for NPM1(mut) MRD assessment that allow for the identification of patients with AML who are at high risk of relapse. Monitoring of NPM1(mut) transcript levels should be incorporated in future clinical trials to guide therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
306
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(331 citation statements)
references
References 31 publications
18
306
1
6
Order By: Relevance
“…The most frequent mutation of the NPM1 gene is found in about 30% of patients with AML. 23 Evaluating NPM1 for measurement of MRD, Krö nke et al 24 showed Non-relapse mortality Relapse Figure 3. Estimates of cumulative incidences of relapse and NRM by chimerism status after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent mutation of the NPM1 gene is found in about 30% of patients with AML. 23 Evaluating NPM1 for measurement of MRD, Krö nke et al 24 showed Non-relapse mortality Relapse Figure 3. Estimates of cumulative incidences of relapse and NRM by chimerism status after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with t(8;21) may have persistent MRD at levels below 0.1%, but still remain in durable complete remissions and possibly cured [48,49]. In patients with non-CBF non-APL AML, some studies have suggested that patients with NPM1 mutations could be monitored quantitatively by PCR studies evaluating NPM1 levels [52,53]. However, most studies of AML without defined translocations have focused on evaluating MRD by multicolor FCM.…”
Section: Measurable Residual Disease In Complete Remission: Methodolomentioning
confidence: 99%
“…Kronke et al further modified this method to show that NPM1 mut levels after double induction and consolidation therapy reflected OS and cumulative incidence of relapse. 197 In 245 patients, PCR negativity had a 6.5% 4-year cumulative incidence of relapse versus 53% for patients with positive PCR. 197 This correlation was also seen when taken after completion of therapy.…”
Section: Rq-pcrmentioning
confidence: 99%
“…197 In 245 patients, PCR negativity had a 6.5% 4-year cumulative incidence of relapse versus 53% for patients with positive PCR. 197 This correlation was also seen when taken after completion of therapy. CEBPA and MLL-partial tandem duplications are two additional targets for MRD monitoring by RQ-PCR.…”
Section: Rq-pcrmentioning
confidence: 99%
See 1 more Smart Citation